Nitrate sources and nitrogen dynamics in a karst aquifer with mixed nitrogen inputs (Southwest China): Revealed by multiple stable isotopic and hydro-chemical proxies. (15th February 2022) - Ren, Kun; Pan, Xiaodong; Yuan, Daoxian; Zeng, Jie; Liang, Jiapeng; Peng, Cong
Highlights: Nitrification is the primary nitrogen transformation process, while denitrification occurs locally. Soil organic nitrogen, nitrogen fertilizer, and manure and sewage are the major NO3 − sources. Nitrification contributes approximately a half to NO3 − flux at the watershed outlet. Abstract: The nitrate (NO3 − ) contamination of karst aquifers as an important drinking water reservoir is increasing globally. Understanding the behavior of nitrogen (N) in karst aquifers is imperative for effective groundwater quality management. This study combined multiple stable isotopes (δ 2 H-H2 O, δ 18 O-H2 O, δ 13 C-DIC, δ 15 N-NO3, and δ 18 O-NO3 ), including hydro-chemical data, with a tracer test and a Bayesian isotope mixing (SIAR) model to elucidate the NO3 − sources and N cycling within the Babu karst aquifer in Guizhou Province, Southwest China. Nitrate isotopes and SIAR model revealed that manure and sewage, nitrogen fertilizer, and soil organic nitrogen were the three dominant NO3 − sources in winter, contributing to 37%, 32%, and 31% to spring NO3 −, and 38%, 31%, and 31% to surface water NO3 −, respectively. The δ 18 O-NO3 values of sampled waters ranging from 0.3‰ to 13.7‰ (mean of 7.7 ± 3.0‰; N  = 63) and the significant negative correlations between δ 15 N-NO3 and δ 13 C-DIC in the spring waters ( P  < 0.01) revealed that nitrification was the primary N transformation process in the Babu watershed. Whereas, denitrification might still occur locally, confirmed by the enriched values of δ 15 N-NO3 (14.3 ± 7.6‰; N  = 6) and high denitrification extent (46.6 ± 22.2%; N  = 6) in the springs from residential areas, and by elevated δ 13 C-DIC (−11.2 ± 0.6‰; N  = 26) and δ 15 N-NO3 values (18.9 ± 5.2‰; N  = 26) in the boreholes. During the base flow period, point-inputs of the AMD-impacted stream and sewage waters, and short transit time (<5 days) were conducive to nitrification processes in the karst conduit, resulting in elevated NO3 − concentration and NO3 − /Cl − ratio at the watershed outlet. Approximately 50% of NO3 − flux at the outlet was derived from nitrification, indicating that a significant extent of nitrification occurred in the NH4 + -contaminated karst conduit, which may be a new NO3 − source to receiving rivers and lakes. This study provided an integrated method for exploring the N dynamics in contaminated karst aquifers. Moreover, the study highlighted that the point N sources control required particular attention for groundwater protection and restoration. Graphical abstract: Image, graphical abstract